Tweak it and freak it : a killer guide to making Windows run your way - McFedries, Paul (Que, 2009)
Tweak It and Freak It A Killer Guide to Making Windows Run Your Way Hundreds of millions of people use Windows every day, and it's a safe bet that some of them would not describe themselves as happy campers. Regardless of skill level, most people have something they dislike about Windows, and they often have a whole laundry list of Windows gripes. "Why can't Windows do this rather than that?" "Why does Windows do X instead of Y?" "Wouldn't it be great if Windows could do Z?" Most people think Windows is set in stone, but it isn't! Strip off that veneer and a whole world comes into view, one that's hackable, moddable, tweakable, customizable, and personalizable. This book shows you the tools and technologies that anyone can use to hack almost every aspect of Windows, from startup to shutdown, from the interface to the Internet, from security to scripting. Speed up your tired PC with a fistful of easy-to-do, but oh so powerful tweaks! Tired of looking at the same old Windows day in and day out? So are we! That's why we show you how to give Windows a makeover! Want to be more productive at work or home? This book is full of productivity tweaks that not only make Windows more fun to use, but also save you tons of time. Create custom backup routines that safeguard your precious data. Tighten the security of your PC and your network to stop would-be thieves in their tracks. Dual-boot Windows XP and Vista on the same machine, or dare we say it, run MacOS on your PC! We won't tell. Paul McFedries is a passionate computer tinkerer and Windows expert. He is the author of more than 60 computer books that have sold more than 3 million copies worldwide. His recent titles include the Sams Publishing books Windows Vista Unleashed, Second Edition, and Windows Home Server Unleashed, and the Que Publishing books Build It. Fix It. Own It.: Networking with Windows Vista, Formulas and Functions with Microsoft Excel 2007, Tricks of the Microsoft Office 2007 Gurus, and Microsoft Access 2007 Forms, Reports, and Queries. Paul is also the proprietor of Word Spy (www.wordspy.com), a website devoted to tracking new words and phrases as they enter the English language. CATEGORY: Windows Operating System COVERS: Windows Vista and XP USER LEVEL: Beginning-Intermediate